1999
DOI: 10.1021/bc990073b
|View full text |Cite
|
Sign up to set email alerts
|

New Donor−Acceptor Pair for Fluorescent Immunoassays by Energy Transfer

Abstract: A novel Förster donor-acceptor dye pair for an immunoassay based on resonance energy transfer (RET) is characterized with respect to its photophysical properties. As donor and acceptor, we chose the long-wavelength excitable cyanine dyes Cy5 and Cy5.5, respectively. Due to the perfect spectral overlap, an exceptionally high R(0) value of 68.7 A is obtained in solution. For biochemical applications, antibodies (IgG) are labeled with Cy5, while a tracer for competitive binding is synthesized by labeling bovine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 40 publications
4
79
0
2
Order By: Relevance
“…These properties are similar to those of the relatively new dye AF647, which has a maximum excitation wavelength of 650 nm, maximum emission wavelength of 670 nm (information from IDT's homepage), and an extinction coefficient of 203000 cm -1 M -1 . 20 According to the manufacturer, the reported fluorescence quantum yields of Cy5 and AF647 dissolved in water are 0.26 21 and 0.33, respectively. In view of these values, AF647 appears to be more fluorescent than Cy5.…”
Section: Detection Of a K-ras Mutation In A Mixture Of Majority Wild-mentioning
confidence: 99%
“…These properties are similar to those of the relatively new dye AF647, which has a maximum excitation wavelength of 650 nm, maximum emission wavelength of 670 nm (information from IDT's homepage), and an extinction coefficient of 203000 cm -1 M -1 . 20 According to the manufacturer, the reported fluorescence quantum yields of Cy5 and AF647 dissolved in water are 0.26 21 and 0.33, respectively. In view of these values, AF647 appears to be more fluorescent than Cy5.…”
Section: Detection Of a K-ras Mutation In A Mixture Of Majority Wild-mentioning
confidence: 99%
“…Furthermore, the europium chelate emits at 613ϳ620 nm, which allows the use of acceptors emitting in the red or near-infrared range. Cy5 has high molar absorptivity at the wavelength of the europium emission and emits red light at 665ϳ670 nm, which is different from the europium emission (28 ). The system thus permits the use of spectral resolution and temporal resolution for the detection of the sensitized acceptor signal.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributable to the formation of nonfluorescent Cy5 dimer. It was previously demonstrated that an increasing Cy5/protein ratio would lead to the formation of nonfluorescent Cy5 dimer within one protein molecule, causing a decrease of the quantum yield (28 ). The highest signal-to-background ratio (32.7) was obtained with albumin labeled with 1.2-1.6 Cy5 molecules/ molecule of albumin.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusions, the results are useful in the correct interpretation of experimental data taking into account both the direct Coulomb interaction of the donor and acceptor electrons and their exchange interaction. This is of particular impotence for measurements of small distance within the biomolecule [2][3][4].…”
Section: Exchange Energy Transfer Ratementioning
confidence: 99%
“…The strong dependence of the energy transfer rate on the distance between the energy donor and the energy acceptor enables to detect the formation of antigenantibody complexes, ensyme-substrate complexes, the DNA hybridization and cleavage [1] and also to study the structure and dynamics of biomolecules, where measurements of small distance within the molecule are necessary [2][3][4]. Results of these investigations are of the great importance for diagnostics and therapy of diseases, among which are oncological ones [5], (see also the literature in [1]).…”
Section: Introductionmentioning
confidence: 99%